Sanctioned Unemployment: The Impact of Occupational Licensing Restrictions on ExOffenders - Annie Zhang (Washington University Journal of Law & Policy, 2018)
This note by Annie Zhang explores how occupational licensing restrictions on ex-offenders create a significant barrier to employment that undermines efforts to rehabilitate offenders and reduce recidivism. Zhang notes that these restrictions are particularly burdensome when they apply to low-income occupations like barbering and cosmetology and proposes that licensing boards be required to consider rehabilitation factors in assessing licensing applications, a direct connection between the conviction and the licensed occupation, and a presumption of licensure for ex-offenders that have completed their vocational training at a correctional facility.
Keywords: ex-offenders; recidivism; employment; licensing; occupational licensing; vocational training; rehabilitation; licensing boards; due process; Equal Protection Clause